Are technology adoption and collective action important in accessing credit? Evidence from milk producers in Tanzania - Twine, Edgar E.; Rao, E.J.O.; Baltenweck, Isabelle; Omore, Amos O. (Springer, 2019)
One of the targets of Sustainable Development Goal 2 is to double agricultural productivity and incomes of small-scale food producers through, among other things, improving access to financial services including credit. However, designing appropriate mechanisms for increasing access to credit by poor households remains a challenge, especially in Sub-Saharan Africa. This paper argues that technology adoption and collective action could provide pathways to enhancing access to credit. Evidence from milk-producing households in Tanzania suggests that group membership increases the probability of borrowing and the amount of funds borrowed by households, while adoption of artificial insemination increases the amount of funds borrowed. Two major conclusions are that public policy for increasing rural households' access to credit should promote collective action, and that the likely increase in amount of funds demanded by households due to technology adoption and collective action will require policy to address issues pertaining to credit rationing of rural households.